2021
DOI: 10.1093/ajcn/nqab219
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal and gluteofemoral fat depots show opposing associations with postprandial lipemia

Abstract: Background High postprandial lipemia is associated with increased risk of cardiovascular disease, independently of fasting lipid concentrations. Abdominal and gluteofemoral fat depots handle lipoproteins differently, which could affect postprandial lipemia and contribute to the relation between abdominal fat distribution and cardiovascular disease risk. Objectives We aimed to study the influences of higher abdominal compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Similarly, de Hollander et al reported that age-adjusted and smoking-adjusted mortality was greater for those with an elevated WC in every BMI category [ 24 ]. It appears that the amount of intra-abdominal adipose tissue—not subcutaneous adipose tissue—critically correlates with the atherogenic and diabetogenic metabolic abnormalities observed among individuals with obesity, an assertion supported by the results of this study [ 25 ]. These findings provide a plausible mechanism by which lower BMI values in an individual with a high-risk WC would entail increased adverse health risk, especially for older adults such as those in our study, whose mean age was 64 years [ 26 ].…”
Section: Discussionsupporting
confidence: 69%
“…Similarly, de Hollander et al reported that age-adjusted and smoking-adjusted mortality was greater for those with an elevated WC in every BMI category [ 24 ]. It appears that the amount of intra-abdominal adipose tissue—not subcutaneous adipose tissue—critically correlates with the atherogenic and diabetogenic metabolic abnormalities observed among individuals with obesity, an assertion supported by the results of this study [ 25 ]. These findings provide a plausible mechanism by which lower BMI values in an individual with a high-risk WC would entail increased adverse health risk, especially for older adults such as those in our study, whose mean age was 64 years [ 26 ].…”
Section: Discussionsupporting
confidence: 69%
“…Furthermore, preliminary analysis within the DIOGenes trial is revealing abdominal and gluteofemoral fat depot influences on postprandial lipaemia. 47 Regarding the predictive role of the metabolic status involving the feedback to dietary interventions, it was possible to identify those patients with a better response to insulin resistance based on the combination of multiple variables (baseline BMI, Matsuda index, lipid concentrations, sex and age). 48 Similarly, patients with higher basal glucose levels had a better response in terms of weight loss influenced by the type of dietary intervention.…”
Section: Discussionmentioning
confidence: 99%
“…This outcome provides additional support to consider TyG index as a surrogate marker of fat content in a feasible approach, as evaluated with DEXA or BIA tools. Furthermore, preliminary analysis within the DIOGenes trial is revealing abdominal and gluteofemoral fat depot influences on postprandial lipaemia 47 …”
Section: Discussionmentioning
confidence: 99%
“…In meta-regression analysis both waist circumference and the waist-to-hip ratio were associated with elevated incident CVD risk in both sexes ( 56 ). Recently, the Brazilian Longitudinal Study of Adult Health reported that a higher lower limb: trunk fat ratio was related to a reduced 10-year cardiovascular risk, mediated by lower systolic blood pressure, lower total cholesterol, and increased HDL-C levels ( 57 , 58 ). Central fat depots contain dysfunctional adipocytes characterized by a pro-inflammatory nature, restricted hyperplasia, and higher turnover of bioactive lipids.…”
Section: Discussionmentioning
confidence: 99%